Yes... according to what I know:)Let
me know if I’m wrong
Answer:
b1 = (2A/ h) - b2
Step-by-step explanation:
A = 1/2 h(b1 + b2)
b1 + b2 = A / 1/2h = 2A/h
b1 = (2A/ h) - b2
We have been given that :-
The length of a parasite in experiment A is
The length of a parasite in experiment B is
Let us write the the length of the parasite in experiment A in the exponent of -3.
Clearly, the length of parasite in experiment A is greater than the length of parasite in experiment B.
The difference in the length is given by
Therefore, the length of the parasite in experiment A is inches greater than the length of the parasite in experiment B.